Platelet-rich plasma for the treatment of postoperative anastomotic fistula of the gastrointestinal tract: a case report - Jia, Sihui; Guo, Yawen; Zhang, Changkai; Sun, Xiaoyuan; Wang, Licun; Wang, Haiyan (Frontiers in Pharmacology, 2026)
IntroductionAnastomotic fistulas are a possible complication of local digestive tract resections, and their main symptoms include abdominal pain, peritonitis, and infections. Currently, the treatment of anastomotic fistulas is primarily conservative or involves surgical repair. Platelet-rich plasma (PRP) contains high concentrations of platelets and is used to promote wound healing. However, the use of PRP in the treatment of anastomotic fistulas has rarely been reported.Case presentationThe patient was a 63 year-old man, Chinese and Asian. The patient underwent radical treatment for a malignant colon tumor in 2011. In 2014, he complained of persistent abdominal pain and was diagnosed with a malignant gastric tumor for which he underwent a subtotal (Billroth I) gastrectomy. After the surgery, an anastomotic fistula was observed. After more than 1 month of conservative treatment, the patient’s anastomotic fistula still failed to heal; then, autologous PRP was attempted. PRP was prepared by centrifugation and activated into a gel state. The fistula was treated with PRP gel occlusion endoscopically, and a total of 3 mL was injected. One week after treatment, the fistula was healed.DiagnosisAnastomotic fistula after subtotal gastrectomy.InterventionsPlatelet-rich plasma (PRP) gel occluded anastomotic fistula under gastroscopy.OutcomesOne week after PRP treatment, the closure of the fistula was observed.ConclusionPRP derived from the patient’s own blood, offers advantages for healing intestinal fistulas that fail to respond to prolonged conservative therapy. Injecting PRP gel directly into these fistulas promotes tissue regeneration and closure.